How to Quickly and Affordably Reduce Corneal Neovascularization: Poster Presentation - Case Report - Resident - Surya Atmaja; Elfa Ali Idrus; Feti Karfiati; Patriotika Muslima; Arief Akhdestira Mustaram; Angga Fajriansyah (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Fine needle diathermy (FND) is one of the treatment modalities for corneal neovascularization (CoNV). Occlusion of the CoNV will reduce vascular leakage, thus preserving visual acuity. This case report presents FND as a treatment for CoNV due to ocular rosacea. Case Illustration : A 25-year-old volleyball athlete came to Cicendo Eye Hospital after experiencing blurry vision for a week, followed by flushing on the face. A general examination revealed telangiectasia and pustules on the central face (Figure 1). Visual acuity was 0.2 RE. A slit-lamp examination revealed hyperemiain the lid margins, oedema, and superficial-stromal neovascularization on the cornea (Figure 2). The patient was diagnosed with blepharo-kerato-conjunctivitis on RE due to ocular rosacea. The patient then underwent FND (Figure 3). The procedure was performed by using a 10.0-gauge needle inserted in the corneal stroma along the CoNV. The vessels were occluded by conducting monophasic diathermy at a power of 1 mA (Figure 4). On the 5th day, corneal oedema and neovascularization were reduced, and visual acuity improved to 0.4 ph 0.5 (Figure 5). Discussion : Corneal neovascularization may affect corneal transparency and thus reduce visual acuity. FND is relatively affordable and widely available. Compared to another modality, FND has not been widely performed to treat CoNV. A literature search using PubMed or Google Scholar found few case reports or reviews regarding successful cases of FND. Conclusion : Fine needle diathermy is a safe and effective treatment for CoNV due to ocular rosacea. Further studies should be conducted to evaluate the safety and long-term efficacy of FND.